Discursive Strategies of a Populist Leader in 2020 Romanian Legislative Elections: The Rhetoric and Political Style of George Simion. (1st October 2022) - Gheorghe, Andrei
Abstract : Rhetoric and the politician's political style are some of his/her most important tools and the technological and media revolution, mobile devices and social networks, have further emphasized their importance. The social networks help politicians to target a very circumscribed audience with their rhetoric, while mobile devices enable them to retain contact with their supporters and to exhibit their political style, in this instance populism. The article examines the speeches of the leader of the Alliance for the Union of Romanians Party (AUR), a new national-populist Romanian party, through the perspective of Chaim Perelman's New Rhetoric and the populist style. The theory developed around the concept of fake news was also used in the development of the argument. According to this theory, the latest developments in the communication industry boosted the fake-news phenomenon, which, in turn, helped the populist leaders. The article is divided into four parts, each part addressing the theory around the new rhetoric; the theory of political style, i.e. populism; the qualitative case study; and the conclusions.